Do We Need the New Testament? - Goldingay, John (Stone-Campbell journal, 2013)
We do need the New Testament, but we need the Old Testament for an understanding of the story of God's working out his purpose, for its theology, for its spirituality, for its hope, for its understanding of mission, for its understanding of salvation, and for its ethics.